Peran Tokoh Agama dalam Menanggulangi Praktik Jual Beli Tuak yang Mengandung Etanol di Kecamatan Maiwa Kabupaten Enrekang - Annisa, Annisa (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2023)
Buying and selling is one of the muamalah activities that is permissible in Islam. However, the issue of halal or haram has received little attention from the public and the government. In this case, the people of Maiwa District, Enrekang Regency need to fulfill their needs by developing business opportunities through the sale of various traditional foods and drinks, including palm wine containing ethanol, where in Islam intoxicants are forbidden to be traded. This research includes empirical research known as social law research. Using a sociological legal approach and qualitatively from the method so that it can produce descriptive data. Data collection techniques through the stages of observation and interviews to answer research questions. The results of the study show that the practice of buying and selling palm wine containing ethanol in Maiwa District is by coming directly to the market and the customer's place. The role of religious leaders in tackling the practice of buying and selling palm wine containing ethanol is by increasing Islamic education and coaching to the community and in terms of Islamic economic law it strictly prohibits this wine from being traded because wine containing ethanol is of course included in khamr or intoxicating drinks.